Games for Peace. Design of Historical Cooperative Games in the Classroom - Federico Peñate Domínguez; Eva Botella Ordinas (Revista Internacional de Educación para la Justicia Social, 2019)
The current paper offers an original methodology in university-based learning on history, focusing on social justice education and the formation of active citizens on peace culture. These deals not only with narratives about the past (identity processes connecting the past with the present through the mechanisms of memory) but also with citizen conscience and process of transition to ecology. Thus, we employ categories and a toolkit drawn from postcolonialism and feminism, while encouraging collaborative work to promote a culture based in peace. The case study is the design of cooperative tabletop games applied in the undergraduate curricula of International Studies and History Grades at Autonomous University of Madrid. In the introduction, we consider the pedagogic methodologies in a context of college education, discussing issues regarding the role of the past in the formation of a globally active citizenship and the training in peace. Secondly, we analyze its relevance for the teaching of history. Thirdly, we explain the methodology followed in our fieldwork and describe both the tools and dynamics employed. The analysis of the resulting data allows us to discuss the results of our research in relation with the initial goals, and how the project can be further improved. Finally, we explain the advantages and disadvantages of applying such a methodology and its future possibilities.